Differences in maturity, morphological and physical attributes between players selected to the primary and secondary teams of a Portuguese Basketball elite academy - Ramos, S.; Volossovitch, A.; Ferreira, A. P.; Fragoso, I.; Massuça, L. (Journal of Sports Sciences, 2019)
The present study aims (i) to compare the maturational, morphological and fitness attributes of young basketball players of primary and secondary teams of an elite basketball academy, and (ii) to identify the set of morphological and fitness attributes which better discriminate the players from the two teams. A total of 116 male basketball players of an elite basketball academy were divided into primary (team A) and secondary (team B) teams in two age groups (U-14 and U-16). All the players were evaluated during two consecutive seasons and data related to players` practice experience, maturational, morphological and fitness attributes were collected at the beginning of the competition period. The results of the study suggest that: (i) in both age categories, team A players were older, more mature, bigger in size and had greater fitness profiles than team B players; (ii) stature and abdominal resistance were identified as discriminant attributes for youth basketball player performance; (iii) aerobic capacity for U-14 and agility for U-16 were identified as specific discriminant attributes for performance in youth basketball. Coaches are recommended to avoid premature talent identification and provide players with opportunities to progress through the talent pathway, at least until U-16 age category.